Comparative analysis of the latest large-scale education reforms in Poland and Hungary - Kristóf Velkey (Facta Simonidis, 2020)
The aim of this study is to present the main features of the reform process in the Hungarian education system after 2010 and comparing it to the Polish education reform started in 2015. The analyzed education systems had common characteristics but since the fall of Communism they have developed differently. Nevertheless, we can observe several significant similarities in comparing the two recent reforms, the most prominent among them are the ways in which the reforms were prepared and implemented. In both cases, a dominant group with sufficient political powers decided to form the national education system in order to correspond to their worldview and political needs.